Sintilimab for the treatment of lung adenocarcinoma-induced immune-related hypophysitis: a case report - Wang, Ming-xing; Liu, Ai-xin; Sun, Qing-ming; Dong, Wan-hui (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) are extensively utilized in the treatment of oncological patients, and the immune-related adverse reactions they induce merit close monitoring. This report describes a case of a lung cancer patient who, after receiving chemotherapy in combination with the programmed death-1 (PD-1) inhibitor sintilimab, presented with systemic fatigue, alterations in mental and behavioral patterns, somnolence, and symptoms of diabetes insipidus, leading to a diagnosis of grade 4 immune-related hypophysitis. The patient experienced symptomatic relief following pulse therapy with dexamethasone sodium phosphate injections (30mg every 12 hours), and was subsequently treated with prednisone acetate tablets (30 mg/day), which were gradually reduced to a physiological replacement dose. The treatment with sintilimab was discontinued, and the patient’s symptoms gradually improved, with normalization of urine output.